East Asian financial market integration: reality or illusions? - S., Ghon Rhee (Penerbit Universiti Kebangsaan Malaysia, 2006)
The 1997·1998 Asian financial crisis, the agenda for local currency bonds and regional bond markets was a priority as an alternative vehicle for domestic saving mobilization and as a means of mitigating the dual mismatch problems of currency and maturity. To achieve this, the East Asian nations will need to be the main players in the regional bond market. Further, the corporation of Japan, China and Korea as the significant players in the regional bond is necessary to provide further liquidity and volume in the markets. The total investment in bond in the ASIAN, excluding Japan is less than one percent of total global bond investment. The potential development of East Asian bond markets is encouraging considering that the markets have increased from us$40l.7b in 1997 to us$I,419.8b in 2004, a 19.8% annual growth. However this is relatively small compared to the sIze of bond markets in other regions. For instance, the relative size of ASlUn bonds outstanding as measured by the percentage of combined GDPs amounted to 40% in 2004. The same figures for Japan, USA and the EU are 190%, 160% and 90% respectively. In the ASEAN region, only Korea and Malaysia have a relatively large corporate bond markets. Most of the bonds in the region are government issued. Issues related to bond market are discussed by looking at the weaknesses and what are needed to encourage the development of the market. Three major concerns are identified; a strong sense of regionalism. overemphasis on the public sector's role and preoccupation with the harmonization of rules and regulations. On the hand, two issues need to be done; the creation of necessary infrastructure and the elimination of Impediments to cross-border investment.